Nr. 1 Affiches. (Hasselt : Provinciaal Museum, 1982)
Boezem, Marinus ; Stockmans, Piet ; De Vree, Paul ; Hamelrijck, Ado ; Johns, Jasper ; Ensor, James ; Lohaus, Bernd ; Dine, Jim ; Dekkers, Ger ; Cortier, Amedée ; etc.
Affiches, Provinciaal Museum, Hasselt, 18.9 - 24.10.1982
boek